Language and Gender Representation in Corporate Social Responsibility: A Case Study of PT Kideco’s Company Profile - Muhammad Khaidirr Nasik; Wilma Prafitri (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
Corporate Social Responsibility discourse serves as a key platform for gender representation in Indonesia's male-dominated mining sector. This study examines linguistic gender patterns in PT Kideco Jaya Agung's Company Profile 2024 using Fairclough's (1992) three-dimensional Critical Discourse Analysis framework. Manual analysis identified 70 gender references across 45 pages, revealing